Effects of exercise on fitness and cognition in progressive MS: A randomized, controlled pilot trial. - Briken, Sven; Gold, Stefan M.; Patra, Stefan; Vettorazzi, E; Harbs, D; Tallner, Alexander; Ketels, Gesche; Schulz, Karl-Heinz; Heesen, Christoph (Multiple Sclerosis Journal, 2014)
Background: Exercise may have beneficial effects on both well-being and walking ability in multiple sclerosis (MS). Exercise is shown to be neuroprotective in rodents and may also enhance cognitive function in humans. It may, therefore, be particularly useful for MS patients with pronounced neurodegeneration. Objective: To investigate the potential of standardized exercise as a therapeutic intervention for progressive MS, in a randomized-controlled pilot trial. Methods: Patients with progressive MS and moderate disability (Expanded Disability Status Scale (EDSS) of 4-6) were randomized to one of three exercise interventions (arm ergometry, rowing, bicycle ergometry) for 8-10 weeks or a waitlist control group. We analyzed the drop-out rate as a measure of feasibility. The primary endpoint of the study was aerobic fitness. Secondary endpoints were walking ability, cognitive function as measured by a neuropsychological test battery, depression and fatigue. Results: A total of 42 patients completed the trial (10.6% drop-out rate). Significant improvements were seen in aerobic fitness. In addition, exercise improved walking ability, depressive symptoms, fatigue and several domains of cognitive function. Conclusion: This study indicated that aerobic training is feasible and could be beneficial for patients with progressive MS. Larger exercise studies are needed to confirm the effect on cognition. © 2014 The Author(s).
Keywords: Aerobic exercise; clinical trial; cognition; depression; fatigue; fitness; motor function; multiple sclerosis; progressive multiple sclerosis; rehabilitation; walking ability